2020
DOI: 10.1186/s12917-020-02618-7
|View full text |Cite|
|
Sign up to set email alerts
|

Bioavailability of subcutaneous and intramuscular administrated buprenorphine in New Zealand White rabbits

Abstract: Background Buprenorphine is one of the most used analgesics for postoperative pain in rabbits. The recommended dose in rabbits (0.01–0.05 mg/kg) is the same for intravenous (IV), intramuscular (IM), and subcutaneous (SC) administration, despite lack of pharmacokinetic data. Five male and five female New Zealand White rabbits (mean ± SD body weight 3.1 ± 0.3 kg) were administered 0.05 mg/kg buprenorphine by the IV, IM and SC routes and 0.1 mg/kg by the SC route, in a cross-over design with two-week wash-out per… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
4
0

Year Published

2022
2022
2023
2023

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 15 publications
(4 citation statements)
references
References 20 publications
0
4
0
Order By: Relevance
“…It is feasible that the amount of SC fat influences the absorption rate due to less vascularization of adipose tissue. The increased skinfold thickness as well as higher BMI has also been associated with delayed absorption of SC administered drugs 54,80–82 …”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…It is feasible that the amount of SC fat influences the absorption rate due to less vascularization of adipose tissue. The increased skinfold thickness as well as higher BMI has also been associated with delayed absorption of SC administered drugs 54,80–82 …”
Section: Discussionmentioning
confidence: 99%
“…The increased skinfold thickness as well as higher BMI has also been associated with delayed absorption of SC administered drugs. 54,[80][81][82] Further, the P-PBPK models were used to predict the dose adjustments for 10-14-year-old children with healthy body weights. For the 10-12-year-old adolescent simulations, 0.25 mg twice weekly dosing for semaglutide would be the preferred indication (Tables 9 and 10).…”
Section: Agementioning
confidence: 99%
“…12,17 Effective analgesia is more likely to be achieved following IM or IV administration due to higher blood plasma levels obtained with these routes. 18 Hydromorphone is a full μ-opioid receptor agonist used to treat moderate to severe pain. Its administration provides analgesia but may also result in mild to moderate sedation in dogs and cats.…”
Section: Clinical Relevancementioning
confidence: 99%
“…Inappropriate injections into thigh muscles could cause nerve damage, and there is a risk of excretion of the injected drug before its absorption due to activation renal portal system controlled by autonomic nervous system in birds [ 4 ]. The absorption of drugs after subcutaneous (SC) injection can be slower as compared to intravenous (IV) administration, resulting in slower onset of action [ 5 ]. Previous studies in birds demonstrated that several classes of sedative–analgesics, such as benzodiazepines, opioids and alpha 2 agonists, are effective when administered intranasally [ 6 , 7 , 8 ].…”
Section: Introductionmentioning
confidence: 99%